The musics of postmodernism - Wołek, Magdalena (Folia Philosophica, 2004)
The author of the article discusses the forms of postmodernism in music. According to her, Wagner was the first great figure of modernism in music. He initiated the aspiration after the overcoming of a tonal system, which was obligatory in music from the half of the 18Ih century. After experimental stages, the musical ways of modernism are exhausted. Minimalism is the first reaction to modernism. Minimalism is numbered among postmodern musical trends. It consists in a repetition of fragments of a given piece. Pieces of historical composers are reinterpreted in postmodernism. The author describes various types of postmodernism in contemporary music and provides examples of such.